Clinical Profile and Outcome of Delirium in Patients in The Semi-Closed Intensive Care Unit - Keyal, Niraj Kumar; Sherpa, Aang Dali; Kumar, Romi; Ansari , Istiyaque (Journal of Nepal Health Research Council, 2025)
Background: Delirium is an underdiagnosed condition in the intensive care unit. This study was conducted to know clinical profile and outcome of delirium in patients in the mixed semi-closed intensive care unit of medical college. Methods: This prospective observational study was done in 284 patients of age≥18 years admitted for more than 24 hours in level three intensive care unit of tertiary care hospital for one year. The Confusion Assessment Method-ICU and Richmond Agitation Sedation Scale were used to diagnose and motor subtype delirium, respectively, Hyperactive delirium was defined as a persistent rating of +1 to +4 during all assessments. Hypoactive delirium was defined as a persistent rating of 0 to −3 during all assessments and mixed subtype was defined as present when the patients have rating of both hyperactive and hypoactive values. There was a checklist to assess risk factors. All data was transferred to the excel sheet and transferred to a statistical package for the social sciences-16. Chi-square test and Fisher’s exact probability test were used to detect the difference between groups in the univariate analysis, as appropriate. Results: Of the 284 ICU admissions 109(38.4%) patients developed delirium. Mixed delirium was the most common motor subtype 39(35.7%) in this study. The mean duration of delirium was 3.69±4.06 days. APACHE II score, SOFA score, presence of co-morbidities, history of alcohol intake, presence of hypoxemia, presence of metabolic acidosis, and use of mechanical ventilation were identified as risk factors for delirium. Delirious patients had longer length of ICU stay (5.8 ±5.4 vs 4.2±4.3 days) and higher reintubation rate. Conclusions: APACHE II score, SOFA score, presence of co-morbidities, history of alcohol intake, presence of hypoxemia, presence of metabolic acidosis, and use of mechanical ventilation were identified as risk factors for delirium in the intensive care unit patients that should be identified early to prevent complication such as longer length of ICU stay and higher reintubation rate. Keywords: Delirium; intensive care units; mortality.